PERFORMANCE ANALYSIS OF MODERN JAVASCRIPT-FRAMEWORKS (Modern information system and technologies, 2018)
In this article, the situation of the frameworks written in JavaScript language for the development of Internet resources was analyzed. The attention paid to the problem of over-saturation of IT-sphere with applications and frameworks of this type. Five most up-to-date JavaScript frameworks are selected. A detailed testing and analysis of the performance testing results was performed. Based on the results, it is concluded that Aurelia is the most productive frame of the year 2017.